Perbandingan Antara Metode RUP dan Prototype Dalam Aplikasi Penerimaan Siswa Baru Berbasis Web - Farid Mubarok; Harliana Harliana; Ijah Hadijah (Creative Information Technology Journal, 2015)
The system of registration and enrollment process that is still using the manual method, the manual registration form hereinafter be recapitulated in the ledger by the committee PSB into the computer. Because the number of applicants who pretty much and continues to grow, so that the input process, data processing and delivery of information resulting from the admission requires substantial time. To overcome this, they invented a new student enrollment applications to facilitate web-based committee in the data processing new admissions and delivery of information with analytical comparison of two methods of software development is the method of RUP and Prototype. In order to obtain a new student registration system with software development method is more accurate in making new student enrollment applications and web-based delivery of desired results in the form of information and reports quickly.The system of registration and enrollment process that is still using the manual method, the manual registration form hereinafter be recapitulated in the ledger by the committee PSB into the computer. Because the number of applicants who pretty much and continues to grow, so that the input process, data processing and delivery of information resulting from the admission requires substantial time. To overcome this, they invented a new student enrollment applications to facilitate web-based committee in the data processing new admissions and delivery of information with analytical comparison of two methods of software development is the method of RUP and Prototype. In order to obtain a new student registration system with software development method is more accurate in making new student enrollment applications and web-based delivery of desired results in the form of information and reports quickly.